Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/jcpe.12528
|View full text |Cite
|
Sign up to set email alerts
|

Bone biology‐related gingival transcriptome in ageing and periodontitis in non‐human primates

Abstract: Aim Cellular and molecular immunoinflammatory changes in gingival tissues drive alveolar bone loss in periodontitis. Since aging is a risk factor for periodontitis, we sought to identify age-related gingival transcriptome changes associated with bone metabolism in both healthy and in naturally-occurring periodontitis. Materials and Methods Adult (12–16 years) and aged (18–23 years) non-human primates (M. mulatta) (n=24) were grouped into healthy and periodontitis. Gingival tissue samples were obtained and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 48 publications
3
30
1
Order By: Relevance
“…The main methods currently used in transcriptomic studies include RNA sequencing and microarray analyses 3,[8][9][10][11][12][13][14][15][16][17][18][19] (Table 1). RNA sequencing effectively demonstrates periodontitis-related gene expression.…”
Section: Tr Anscrip Tomic Smentioning
confidence: 99%
See 1 more Smart Citation
“…The main methods currently used in transcriptomic studies include RNA sequencing and microarray analyses 3,[8][9][10][11][12][13][14][15][16][17][18][19] (Table 1). RNA sequencing effectively demonstrates periodontitis-related gene expression.…”
Section: Tr Anscrip Tomic Smentioning
confidence: 99%
“…Specifically, genes related to osteoclast function exhibit enhanced expression (secreted phosphoprotein 1, toll like-receptor 4, matrix metallopeptidase 8, and transcription factor EC), and those related to osteoblast activity are impaired (protein phosphatase 4 regulatory subunit 3C and SMAD family member 5). 14 The effects of smoking on the periodontium have been widely investigated in clinical and animal studies. [21][22][23] Transcriptomic studies have revealed that smoking mediates epigenetic modifications on the extracellular matrix organization of the periodontium, which subsequently enhances disease progression and accelerates tissue destruction.…”
Section: In Vitromentioning
confidence: 99%
“…Resulting DNA damage, lipid peroxidation, protein, other important enzyme oxidation and stimulation in the release of proinflammatory cytokines by monocytes and macrophages. Inflammatory chronic induce collagen breakdown, RANKL, osteoclast stimulation until alveolar bone resorption (Pandruvada, 2016).…”
Section: B Correlation Gingivitis With Sle Severitymentioning
confidence: 99%
“…In SLE patients the occurrence of hyperactivity of dendritic cells and hypoactivity of T-cell reg. Hypoactivity of Treg cells causes directly killing itself and vulnerable to infection (Pandruvada, 2016).…”
Section: B Correlation Gingivitis With Sle Severitymentioning
confidence: 99%
“…Alterations in gene expression in periodontitis particularly in aged animals were skewed towards creating an environment with substantial osteoclastogenic potential consistent with the bone resorption in periodontitis (Supplemental Figure 2). These data indicated that local bone resorptive processes are up-regulated under the condition of aging creating a tissue destructive environment [134]. More recently, we evaluated the potential interaction between human antibody responses to P. gingivalis and activation of osteoclasts (OC) as an entry point into more critical definition of how these antibodies might function in health and disease.…”
Section: Aging and Osteoimmunologymentioning
confidence: 99%